Effects of estradiol benzoate injection to intact and castrated male rabbits on LH, FSH, testeosterone and prostate tissues - Elkhier, Tamour; Hassaballa, Shams-Eldein; Omer, Shadia Abdo-Elatti; Adam, Abdelnasir (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: This study was conducted to investigate the effects of estradiol benzoate injection to intact and castrated male rabbits on LH, FSH, testosterone and prostate tissue. Materials and methods: A total of 72 mature male rabbits were used in this study. The rabbits were randomly divided into two groups (36 intact and 36 castrated) and each group was further divided into four sub-groups. The rabbits of each subgroup were injected estradiol benzoate dosed at 0, 40, 80 and 120 µgm/rabbit, through intramuscular (IM) route, on each alternative day over a period of 30 days. The levels of LH, FSH, and testosterone were measured in serum samples. Prostate tissue samples were taken from each sub-groups, histological examination was done. Results: The mean serum levels of LH and FSH were not affected by injection of estradiol benzoate in all intact and castrated rabbits sub-groups (P>0.05). However, the results of testosterone levels were showed insignificant increase in all intact and castrated male rabbits sub-groups, except the intact male rabbit sub-group that received estradiol benzoate at 120 µg/rabbit (P<0.05). Furthermore, the effects of estradiol benzoate in prostate tissues were ranged from hyperplasia with dysplasia or dysplasia only in intact male rabbits; hyperplasia was represented by papillary projection in castrated male rabbits. Conclusion: The present study revealed no difference in the serum levels of LH, FSH in intact or castrated male rabbits, however, testosterone hormone did not show any change except in sub-group of intact male rabbits that was injected dosed at 120 µg estradiol benzoate. The effect of estradiol benzoate on prostate tissue was found to be induce hyperplasia in both intact and castrated males rabbits.